Угрюм - река: роман / В. Я. Шишков - Шишков Вячеслав Яковлевич (Русская классика, 2012)
Экземпляры: аб. ЦБ (2018.03.05) / Инвентарный номер: 4346 / Цена: / Сис.шифр: 84(2Рос-Рус)6 / Авт.знак: Ш55 / ББК: 84(2Рос-Рус)6